2019
DOI: 10.1038/s41598-019-39622-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism A118G of opioid receptor mu 1 (OPRM1) is associated with emergence of suicidal ideation at antidepressant onset in a large naturalistic cohort of depressed outpatients

Abstract: Antidepressants have been the object of an international controversy for about thirty years. Some patients are inclined to develop suicidal ideation (SI) at antidepressant onset; this phenomenon is known as Treatment Emergent Suicidal Ideation (TESI), and it has conducted regulatory bodies to prompt warnings on antidepressants. Since, few studies have explored the pharmacogenomics of TESI. Given the growing body of evidence connecting the opioidergic system with suicidal behavior (particularly mu opioid recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…SPAG17 (sperm-associated antigen 17) was previously identified by whole exome sequencing of suicide deaths as a locus enriched for rare variants ( Tombacz et al, 2017 ). OPRM1 encodes the mu-opioid receptor 1 and has garnered considerable attention in candidate gene and large-scale genetic studies of several psychiatric disorders and suicidal ideation ( Nobile et al, 2019 ) and suicidal behavior ( Arias et al, 2012 ). We also detected inhibitory neurons from layers 2–5 of the middle temporal gyrus expressing both SCUBE3 and PVALB .…”
Section: Discussionmentioning
confidence: 99%
“…SPAG17 (sperm-associated antigen 17) was previously identified by whole exome sequencing of suicide deaths as a locus enriched for rare variants ( Tombacz et al, 2017 ). OPRM1 encodes the mu-opioid receptor 1 and has garnered considerable attention in candidate gene and large-scale genetic studies of several psychiatric disorders and suicidal ideation ( Nobile et al, 2019 ) and suicidal behavior ( Arias et al, 2012 ). We also detected inhibitory neurons from layers 2–5 of the middle temporal gyrus expressing both SCUBE3 and PVALB .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a single suicide item from a depression rating scale is a valid approach to assess SI compared with the Scale for Suicide Ideation (Desseilles et al, 2012). This method was previously used in large clinical studies, such as the STAR*D (Zisook et al, 2009), and also in more recent studies (Bernert et al, 2017; Nobile et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a role has been recognized for the A118G SNP in mediating affiliative behavior, such as affectionate relationships and attachment (Nobile et al., 2019; Troisi et al., 2011). Importantly, it has been shown that this SNP is involved in social attachment and the social reward system in children (Copeland et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the research in this field has focused on the A118G polymorphism and on several psychopathological traits, such as stress response, social anhedonia (Lovallo et al., 2015; Troisi et al., 2011), and heightened sensitivity to social rejection (Way et al., 2009), and on psychopathologies such as addictive behaviors, depression, and suicide (Kennedy et al., 2006; Nobile et al., 2019; Schwantes‐An et al., 2016), no studies have confirmed its association with the disruptive mood dysregulation disorder (DMDD) in school‐age youths. This clinical condition has a prevalence of 2%–5% in pediatric psychiatric populations, and it has been recently included among the depressive disorders in DSM‐5 (American Psychiatric Association, 2013), being characterized by a severe impairment in the emotion and behavioral regulatory processes.…”
Section: Introductionmentioning
confidence: 99%